A case of pretibial myxedema associated with hypothyroidism and thyroid-stimulating hormone receptor antibodies - Sang Yong Oh; Han Kyoung Cho; Yoon Yang Jung; Min-Kyung Lee (Wolters Kluwer Medknow Publications, 2019)
Pretibial myxedema (PTM) is an infiltrative dermopathy seen in Graves' disease. It is also infrequently associated with hypothyroidism. Here, we describe a rare case of PTM with hypothyroidism in which thyroid-stimulating hormone receptor antibodies were found. An 82-year-old female presented with a 1-year history of a large pruritic plaque which was present over both her legs and feet. Histopathology of a skin biopsy showed markedly increased dermal mucin. These changes were suggestive of PTM. This case provides evidence that an autoimmune mechanism could play a central pathogenetic role in such cutaneous manifestations.